Body and wing size, but not wing shape, vary along a large-scale latitudinal gradient in a damselfly - David Outomuro (Nature Portfolio, 2021)
Abstract Large-scale latitudinal studies that include both north and south edge populations and address sex differences are needed to understand how selection has shaped trait variation. We quantified the variation of flight-related morphological traits (body size, wing size, ratio between wing size and body size, and wing shape) along the whole latitudinal distribution of the damselfly Lestes sponsa, spanning over 2700 km. We tested predictions of geographic variation in the flight-related traits as a signature of: (1) stronger natural selection to improve dispersal in males and females at edge populations; (2) stronger sexual selection to improve reproduction (fecundity in females and sexual behaviors in males) at edge populations. We found that body size and wing size showed a U-shaped latitudinal pattern, while wing ratio showed the inverse shape. However, wing shape varied very little along the latitudinal gradient. We also detected sex-differences in the latitudinal patterns of variation. We discuss how latitudinal differences in natural and sexual selection regimes can lead to the observed quadratic patterns of variation in body and wing morphology via direct or indirect selection. We also discuss the lack of latitudinal variation in wing shape, possibly due to aerodynamic constraints.